2021
DOI: 10.4028/www.scientific.net/msf.1034.187
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Basalt Fiber in Lightweight Expanded Clay to Improve the Strength of Concrete Helicoidal Staircase

Abstract: Staircase is a very important structural element found in mostly buildings of more than a floor. The properties of materials and designs used in constructing this structural element are very important. This study addresses the development of ultra-lightweight concrete. How ultra-lightweight concrete can effectively work in helicoidal structure. The flexural strength of this staircase was analysed on a finite element software SCAD. The designed lightweight aggregates concrete is targeted to be used in staircase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The development of BF was first performed by the Moscow Research Institute of Glass and Plastic in 1953–1954, and its first industrial production furnace was completed in 1985 at a Ukraine fiber laboratory [ 1 ]. The fibers of basalt provide resistance against corrosion, heat, and chemical attack on the concrete, making them beneficial for use in building materials [ 2 , 3 , 4 , 5 , 6 , 7 ]. Previous studies have shown that BF is able to enhance the mechanical characteristics of concrete [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of BF was first performed by the Moscow Research Institute of Glass and Plastic in 1953–1954, and its first industrial production furnace was completed in 1985 at a Ukraine fiber laboratory [ 1 ]. The fibers of basalt provide resistance against corrosion, heat, and chemical attack on the concrete, making them beneficial for use in building materials [ 2 , 3 , 4 , 5 , 6 , 7 ]. Previous studies have shown that BF is able to enhance the mechanical characteristics of concrete [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the results of adding BF to HSC and HPC are shown by the significant increase in flexural and tensile strength and the improvement of concrete durability [ 5 , 7 , 15 ]. Moreover, including mechanical aspects, BF has economic aspects as an alternative material to increase the mechanical properties of HPC [ 16 ]. For example, Hematibahar [ 17 ] investigated adding BF to HPC.…”
Section: Introductionmentioning
confidence: 99%